2004
DOI: 10.1074/jbc.m405003200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cell Wall Mannosylphosphate in Candida albicans Does Not Influence Macrophage Recognition

Abstract: The outer layer of the cell wall of the human pathogenic fungus Candida albicans is enriched with heavily mannosylated glycoproteins that are the immediate point of contact between the fungus and cells of the host, including phagocytes. Previous work had identified components of the acid-labile fraction of N-linked mannan, comprising ␤-1,2-linked mannose residues attached via a phosphodiester bond, as potential ligands for macrophage receptors and modulators of macrophage function. We therefore isolated and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
139
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(158 citation statements)
references
References 63 publications
10
139
2
1
Order By: Relevance
“…Loss of O-mannan has been shown to result in reduced adherence and the attenuation of virulence, suggesting that O-mannan may act as a ligand in the interaction with host surfaces (12, 14, 28 -31). Conversely, phosphomannan has been shown not to be required for normal host-fungal interactions or virulence (32). We have extended these studies by analyzing the importance of the N-glycan outer chain epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of O-mannan has been shown to result in reduced adherence and the attenuation of virulence, suggesting that O-mannan may act as a ligand in the interaction with host surfaces (12, 14, 28 -31). Conversely, phosphomannan has been shown not to be required for normal host-fungal interactions or virulence (32). We have extended these studies by analyzing the importance of the N-glycan outer chain epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Cells Cell Wall Analysis and Sensitivity Testing-Alcian blue binding was assayed essentially as described previously (27,32). A suspension of ϳ1 ϫ 10 7 stationary phase yeast cells was washed and resuspended in 1 ml of 30 g/ml Alcian blue in 0.02 M HCl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphomannan has been implicated in the interaction of C. albicans with macrophages. However, deletion of the C. albicans MNN4 gene, which is required for mannosyl phosphate transfer, demonstrated that phosphomannan is not required for macrophage interactions or virulence of C. albicans (26). Genes such as…”
mentioning
confidence: 99%
“…Furthermore, an interesting observation is that members of the BMT gene family are present in only a limited number of known fungal species, but among these is the prominent fungal pathogen A. fumigatus (60). Despite these findings, recently published papers have contradicted this notion and led to the conclusion that ␤-Man may actually have little effect on C. albicans virulence (20,21). However, the strategy followed in these papers did not specifically target ␤-Man, but rather was based on the inactivation of C. albicans genes, homologous to S. cerevisiae genes, which prevented downstream association of ␤-Man to PPM (20,21).…”
Section: Discussionmentioning
confidence: 99%